Carbon turnover and microbial activity in an artificial soil under imposed cyclic drainage and imbibition - Pronk, G.J. (2020)
At the end of the experiment, the fluctuating water table columns exhibited a distinct zone of organic C (OC) depletion in the depth interval of 8–20 cm that was not observed under the static regime. Although this zone showed elevated levels of adenosine triphosphate (ATP), the microbial biomass was actually lower than at the corresponding depth interval of the static regime. A vertically stratified microbial community established in all columns that depended on oxygenation with depth. The 16S ribosomal RNA (rRNA) gene analyses showed a slightly higher diversity in the soil exposed to moisture fluctuations, but there was no clear difference in major taxa and microbial community composition between treatments. These results thus suggest that the localized enhancement of OC degradation induced by the water table fluctuations was driven by a more active, rather than a more abundant or compositionally very different, microbial community.